Tangible temptation in the social dilemma: Cash, cooperation, and self-control - Kristian Ove R. Myrseth; Gerhard Riener; Conny Wollbrant (European School of Management and Technology (ESMT), 2013)
The social dilemma may contain, within the individual, a self-control conflict between urges to act selfishly and better judgment to cooperate. Examining the argument from the perspective of temptation, we pair the public good game with treatments that vary the degree to which money is abstract (merely numbers on-screen) or tangible (tokens or cash). We also include psychometric measures of self-control and impulsivity. Consistent with our hypothesis, we find in the treatments that render money more tangible a stronger positive association between cooperation and self-control - and a stronger negative association between cooperation and impulsivity. Our results shed light on the conditions under which self-control matters for cooperation.
urn:nbn:de:101:1-201307108803
Keywords: D01; D03; D64; D70; 650; Self-control; pro-social behavior; public good experiment; temptation